Provision of barrier-free environment at waterfront development in Malaysia - Shamsuddin, Shuhana; Abdullah, Fadzidah; Mohd Amin, Ruzita (2009)
Development of waterfronts worldwide began in the 1970s, with the commercial success of development in Boston and Baltimore. Waterfront development that incorporates recreational facilities serves as a tourist attraction and provides a means to increasing the quality of life of people. Hence, access to such development for all members of the society including people with disabilities (PwDs) is important in order for them to also enjoy the benefits of the waterfronts. To investigate whether waterfront areas in Malaysia provide barrier-free environment for PwDs, this study undertakes an access audit in three selected waterfronts in Malaysia, namely, Danga Bay in Johor Bahru, Johor, Kota Kinabalu Waterfront in Sabah, and Kuching Waterfront in Sarawak. The study found that all the three waterfront areas are still lacking in terms of meeting accessibility needs of PwDs. Among the common problems observed is lack of attention to details in terms of drop levels, ramps, curbs and paving materials. Public amenities designated for PwDs such as toilets and parking spaces are either entirely nonexistent or do not comply with the specified Malaysian standards. The existence of too many obstructions on pathways poses as an additional danger to the vision-impaired. Both wheelchair users and those using crutches who participated in the access audit found the waterfront area to be very challenging. Hence, a comprehensive improvement of the waterfront areas is certainly needed to ensure full accessibility by all including PwDs to ensure equal opportunities for everyone.